Komunikasi Public Relations dalam Program Corporate Social Responsibility Talent Udjo - Dwi Putri Budiawan; Maman Suherman (Bandung Conference Series: Public Relations, 2023)
Abstract. Government policies oblige companies to carry out CSR programs in the environment around the company aiming to bring companies closer to the community. PT. Saung Angklung Udjo dedicates its CSR program "Talent Udjo" to students who become the foundation of hope for parents to be able to change their family's economy. With this phenomenon the researcher intends to find out how PR communicates in the Udjo talent CSR program. In this study using qualitative methods with a case study approach, using the constructivism paradigm. Then, data sources were obtained through interviews, observation, and documentation in the field. Data analysis will be carried out using data reduction analysis techniques, data presentation, and drawing conclusions. Describes that public relations communication in the talent udjo CSR program has not really shown the implementation of a PR practitioner. The CSR program that has been created long ago has not changed the position of a public relations officer at PT. Saung Angklung Udjo. The creation of the Udjo talent CSR program has the intention of being a form of his love for the preservation of culture from West Java which is made of bamboo to empower the community which has been maintained until now so as to create generations of children of the nation who are increasingly developing with the priority of school dropouts. Internal and external communications created by public relations must be good. Public relations is believed to be the face of the company in receiving guests and giving a friendly impression to visitors. Coffee morning is held as an evaluation of employee divisions in order to establish closer relationships. @saungangklungudjo is an Instagram social media account owned by PT. Saung Angklung Udjo in promoting and disseminating information, but in the CSR talent program, Udjo still uses a word of mouth strategy in attracting children who will join. Abstrak. Kebijakan pemerintah mewajibkan perusahaan untuk melaksanakan program CSR di lingkungan sekitar perusahaan bertujuan untuk mendekatkan perusahaan dengan masyarakat. PT. Saung Angklung Udjo mendedikasikan program CSR ”Talent Udjo” kepada anak-anak didik yang menjadi tumpuan harapan para orang tua untuk bisa merubah perekonomian keluarganya. Dengan fenomena ini peneliti bermaksud untuk mengetahui bagaimana komunikasi PR dalam program CSR talent udjo. Pada penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, menggunakan paradigma konstruktivisme. Kemudian, sumber data diperoleh melalui wawancara, observasi, serta dokumentasi di lapangan. Data analisa yang akan dilakukan dengan menggunakan teknik analisis reduksi data, penyajian data, dan penarikan kesimpulan. Mendeskripsikan bahwa komunikasi public relations dalam program CSR talent udjo belum terlalu memperlihatkan implementasi dari seorang praktisi PR. Terciptanya program CSR talent udjo memiliki maksud sebagai bentuk kecintaannya terhadap pelestarian kebudayaan asal Jawa Barat yang terbuat dari bambu untuk memberdayakan masyarakat yang dipertahankan hingga saat ini agar terciptanya generasi-generasi anak bangsa yang semakin berkembang dengan prioritas anak putus sekolah. Komunikasi internal dan external yang diciptakan oleh public relations haruslah baik. Public relations dipercaya sebagai wajah bagi perusahaan dalam penerimaan tamu dan memberikan kesan ramah terhadap para pengunjung. Coffe morning diadakan sebagai evaluasi para divisi karyawan agar dapat menjalin hubungan lebih erat. @saungangklungudjo merupakan akun media sosial Instagram yang dimiliki oleh PT. Saung Angklung Udjo dalam mempromosikan dan menyebarkan informasi, namun dalam program CSR talent udjo masih menggunakan strategi mulut ke mulut dalam menarik anak-anak yang akan bergabung.